Estimates of body size and body mass in Caimaninae from the Miocene of South America, and contributions to their physiology - Paiva, Ana Laura da Silva (2021)
Crocodyliforms are a clade of Archosauria that originated in the late Triassic, containing a wide array of extinct and extant species, especially the crown-group Crocodylia, which diversified in the Cenozoic. The group includes the living gharials, crocodiles, alligators, and caimans, in addition to the extinct representatives. Among those, the Crocodylia species of the Miocene of South America are known for their peculiarities, such as cranial shape and greatly varying body size, as well as distinct behavioral and ecological niches. Regarding the crocodyliform lineage exist several studies about their evolutionary history, ecology, and body shape, mainly within Caimaninae. This group was morphologically diverse, which could be explained by biotic and abiotic factors in the middle and late Miocene, suggesting an opportunity to better study the evolutionary history. They can be found in three main geological units: Honda Group (Colombia), Solimões Formation (Brazil), and Urumaco Formation (Venezuela), which shared similar biodiversity and paleoenvironment. In particular, three species demonstrate this rich diversity of the group in the epoch: Acresuchus, Mourasuchus, and Purussaurus. Estimates of the total length and body mass of fossil Caimaninae are important to understand ecological and physiological factors that could have impacted their body size evolution. More than that, in many other groups of ectothermic animals, the body mass is correlated with abiotic factors. The first chapter of this dissertation will give a brief overview of the Crocodyliforms, especially Caimaninae, and their different morphotypes. In the second chapter, biotic factors related to body size and mass of three fossil caimanines will be analyzed, discussing their implications and comparing different methods for the estimation of body size and mass. The third chapter uses the abiotic factor of paleotemperature to discuss the thermophysiology of large extinct caimanine crocodilians.